Comparison of Two Learning Models on Students' Process Skills in Elementary School - Kamid; Roseli Theis; Sufri; Sabila Eka Septi; Fhadira Insani Putri (Jurnal Ilmiah Sekolah Dasar, 2022)
The learning model is one of the most important things in the learning and learning process. A good learning model will make students more enthusiastic in learning because the model is interesting and effective. The purpose of this study was to analyze the comparison of learning models of problem based learning and problem solving models with student problem solving on cube and block material on the skill process in elementary schools. The method used in this study is a quantitative method with a comparative type. The population of this study was 72 students from two schools, included 40 women and 32 men as students, were the subjects studied. The instruments used are student process skills observation sheets and learning questionnaire models. Data collection techniques used in this study were questionnaires and observation sheets. The data analysis technique used is purposive sampling. The results of the description can be said that based on the T test it can be said that the problem-solving learning model is superior to the problem-based learning model. From the results of the T test for the learning model of students' science process skills, it can be seen that there are differences in the learning model.